WANPRESTASI DALAM PERANJIAN CARTER KAPAL ANTARA PT. PELAYARAN BATAMITRA SEJAHTERA DENGAN PT. KHARISMA INTI MULIA: Form of Loss in the Event of Breach of Performance in the Charter Agreement - Renita Tobing; Elfrida Ratnawati (Reformasi Hukum Trisakti, 2024)
The case raised in this thesis research is a breach of contract in the charter agreement between PT,. The problem is: are there any defaults in Carter Agreement No. 018/SPAL-TC/PBS-KIM/X/2020? And what form of compensation is due to PT's default? Kharisma Inti Mulia towards PT. Batamitra Sejahtera Shipping in Carter Agreement No. 018/SPAL-TC/PBS-KIM/X/2020? Main problem this research is using a normative research, analytical description with secondary data, then the data is analyzed qualitatively by drawing conclusions using deductive logic. The results and conclusion of this article that there was a breach of contract committed by PT. Kharisma Inti Mulia towards PT. Pelayaran Batamitra Sejahtera and can apply Article 1238 of the Civil Code. PT. Kharisma Inti Mulia has committed a breach of contract by not paying the amount that should be stipulated in a valid agreement, namely Ship Transport Agreement Letter No. 018/SPAL-TC/PBS-KIM/X/2020, which resulted in material and immaterial losses to PT. Batamitra Sejahtera Shipping. The charterer did not show good faith in providing compensation until this lawsuit was submitted to the Batam District Court.